2014
DOI: 10.1111/fwb.12321
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐induced changes in lipid biomarkers and mycosporine‐like amino acids in the psychrophilic dinoflagellate Peridinium aciculiferum

Abstract: Summary Life at low temperature imposes many constraints linked to sustaining cellular functions. The cold‐adapted freshwater dinoflagellate Peridinium aciculiferum has overcome these barriers, often causing blooms in winter but forming resting cysts in spring. Little is known of the biochemical changes that accompany this temperature‐induced transformation from vegetative cells to resting cysts. We investigated how the profiles of lipids and mycosporine‐like amino acids (MAAs) vary with temperature in veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 85 publications
0
60
0
Order By: Relevance
“…triacylglycerols, phospholipids, galactolipids, and betaine lipids (Flaim et al, 2014). The lipids separated by TLC and determined in two Symbiodinium strains included DGDG, SQDG, PC, PE, cardiolipin (CL), MGDG, and PG, including five unknown lipid classes.…”
Section: Separation and Identification Of Lipid Classesmentioning
confidence: 99%
See 3 more Smart Citations
“…triacylglycerols, phospholipids, galactolipids, and betaine lipids (Flaim et al, 2014). The lipids separated by TLC and determined in two Symbiodinium strains included DGDG, SQDG, PC, PE, cardiolipin (CL), MGDG, and PG, including five unknown lipid classes.…”
Section: Separation and Identification Of Lipid Classesmentioning
confidence: 99%
“…Betaine lipids such as diacylglycerylcarboxy-Nhydroxymethylcholine (DGCC) were found to contain highly unsaturated molecular species of the types 44:15-and 46:15-DGCC (Flaim et al, 2014) or 44:12-DGCC (Leblond et al, 2015) while diacylglyceryltrimethyl-homoserine (DGTS) was found to contain only saturated and monoenoic species, e.g. 32:1-DGTS (Leblond et al, 2015).…”
Section: Separation and Identification Of Lipid Classesmentioning
confidence: 99%
See 2 more Smart Citations
“…Adaptation mechanisms are therefore required for any living organism, and they have been studied extensively for higher plants already [1,2]. However, micro and macro algae and cyanobacteria follow different strategies and several unique constituents for UV protection are known in this respect [3,4,5,6]. Mycosporine-like amino acids (MAAs), a group of small water-soluble compounds are especially relevant.…”
Section: Introductionmentioning
confidence: 99%